Reading Interest and Motivation in English Education at Junior High School - Agustina, Giska; Mandarani, Vidya; Syaputra, Reza Dwi; Nujum, Idbaaron; A., Ongky Giovanny Bagus (Procedia of Social Sciences and Humanities, 2024)
This study aims to explore students' interest and motivation in reading in English language learning at Junior High School. A qualitative approach was used to gain an in-depth understanding of this interest and motivation in reading. Data was collected through classroom observations, interviews with English teachers, and interviews with students. The results showed that reading interest and motivation have a significant impact on students' English learning achievement. The findings provide an in-depth understanding of how a learning approach that focuses on increasing interest and motivation to read can improve English learning outcomes in junior secondary schools. The implication of this finding is the need to develop learning strategies that can encourage students' interest and motivation in reading, as well as increased cooperation between teachers, students, and educational stakeholders to create a supportive learning environment.